Dasar-dasar Pendidikan Islam Modern dalam Filsafat Iqbal - Muhammad Mukti (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Iqbalâ€™s Islamic education basic principle properly entitled â€œmodernâ€ because he has trying to synthesize education. This kind of education is not traditional education (orthodox and Sufi) and not modern education ala West an sich, but education that have direction to form human being, creating human character that not only â€œknowingâ€ but also creative and dynamic, that enhance human values and specifically Islamic spiritual culture. Therefore, Iqbal principle of thought has correlation with recent modern education nowadays.